Pelvic Congestion Syndrome – Findings on Multi-Detector Row Computerized Tomography: A Case Report - Shi-Zuo Liu; Chen-Pin Chou; Jer-Shyung Huang; Huay-Ben Pan (Kaohsiung Journal of Medical Sciences, 2003)
Chronic pelvic pain is a common gynecologic complaint, sometimes without any obvious etiology. We report a case of pelvic congestion syndrome with chronic pelvic pain. The diagnosis can be overlooked by clinical physicians but diagnosed using multi-detector row computerized tomography. This method seems to be an effective and non-invasive imaging modality.